1998
DOI: 10.1051/rnd:19980309
|View full text |Cite
|
Sign up to set email alerts
|

Selective in vitro degradation of the sialylated fraction of germ-free rat mucins by the caecal flora of the rat

Abstract: -Mucins, which are synthesized throughout the gastrointestinal tract, may be degraded by the microflora of the large intestine. The present study was undertaken to determine the differential fate of the various types of mucins. Mucins from germ-free rats were incubated in vitro in the presence of whole caecal flora from the conventional rat. Neutral, acidic and acidic sulphated mucins were spectrophotometrically assayed over time upon anaerobic incubation. Sialylated mucins were more rapidly degraded (90 %)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although the physiological role of distinct mucin subtypes is not well understood, the state of "health" of the gut seems to be related to the degree of mucin maturation with sulfated acidic mucin considered as more mature and so more protective for the gut (Fontaine et al, 1998). The present results might imply no change in the capacity of mucus to protect the gut against bacterial infection.…”
Section: Resultsmentioning
confidence: 60%
“…Although the physiological role of distinct mucin subtypes is not well understood, the state of "health" of the gut seems to be related to the degree of mucin maturation with sulfated acidic mucin considered as more mature and so more protective for the gut (Fontaine et al, 1998). The present results might imply no change in the capacity of mucus to protect the gut against bacterial infection.…”
Section: Resultsmentioning
confidence: 60%
“…In the small bowel of Klf4 mutant mice, there is a reduction in staining for acidic mucin (as demonstrated by the Alcian blue stain) but no change in staining for neutral mucin (as demonstrated by the PAS stain) and the goblet cell-specific marker, Muc2. As acidic mucin is considered the more mature form of mucin produced by goblet cells (Fontaine et al, 1998), these findings suggest that Klf4 is required for maturation of goblet cells in the small intestine. In the colon, Klf4 is required not only for the maturation but differentiation of goblet cells as demonstrated by the significant reduction in the number and size of goblet cells, as well as in staining for Muc2, and both acidic and neural mucins in the colon of Klf4 ΔIS mice compared to controls (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In one study mucins from germ-free rats were incubated with total cecal microbiota from conventionally raised rats. Sialylated mucins were degraded more rapidly than the neutral or sulfated forms suggesting an overall optimized use of sialic acids by intestinal bacteria [72]. Although ocular fluid from many humans is sterile, some studies have shown that other people maintain a commensal bacterial population without incident.…”
Section: The Salad Bar-substrate Availability At Mucosal Surfacesmentioning
confidence: 99%